THE CRUELTY IN SCHOOL COMMUNITY IN JAY ASHER’S THIRTEEN REASONS WHY - Lidyawati Mangangawuhi; Tini Mogea; Agustine C. Mamentu (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2022)
The purpose of this research is to reveal the cruelty in school community in the novel Thirteen Reasons Why. The writers use qualitative research method. In conducting this research, the authors collected data into two categories. Primary sources and secondary sources, primary sources are the novels themselves, by Jay Asher's Thirteen Reasons Why novels and secondary sources are other related documents such as related books, dictionaries, internet browsing, other literary works and sources that support the analysis and to analyze data, the authors using an objective approach. The results of this study indicate the Jay Asher‟sThirteen Reasons Why novel is arguing about the cruelty. The cruelty experienced by the main character is sexual harassment and rumours that the main character is a prostitute. The cause of cruelty is disappointment and feeling persecuted.In the world of education; teachers must teach students that cruelty is bad and should not be done. Wherefore, the teacher can explain consequence of cruelty that must be received by people who commit cruelty.